The clinicopathological and molecular analysis of gastric cancer with altered SMARCA4 expression. Issue 2 (2nd July 2020) - Huang, Shih‐Chiang; Ng, Kwai‐Fong; Yeh, Ta‐Sen; Cheng, Chi‐Tung; Chen, Min‐Chi; Chao, Yi‐Chun; Chuang, Huei‐Chieh; Liu, Yu‐Jen; Chen, Tse‐Ching
Abstract : Aims: In this study, we examine the clinicopathological and molecular features of gastric cancer (GC) with SMARCA4 alterations. Methods and results: We screened SMARCA4 alterations using immunohistochemistry on 1199 surgically resected GCs with information on Epstein–Barr virus (EBV), microsatellite instability (MSI) and other SWI/SNF subunits. SMARCA4, SMARCA2 and ARID1A mutations were investigated by targeted sequencing. The clinicopathological significance was determined by statistical analysis. Twenty‐seven cases (2%) with altered SMARCA4 expression were identified, exhibiting completely lost (six), reduced (nine) or heterogeneous (12) patterns. Frequent concomitant alterations of other SWI/SNF subunits were noted with an unusual discordant spatial heterogeneity. In comparison with SMARCA4‐retained GCs, SMARCA4‐lost GCs were observed more frequently in the non‐EBV/MSI subgroup (five of six) and reduced or heterogeneous SMARCA4 expression mainly occurred in EBV‐ or MSI‐associated cases (six of nine and six of 12, respectively; P  < 0.001). Histologically, SMARCA4‐altered GC, irrespective of expression pattern, demonstrated divergent histomorphology, spanning tubular, poorly cohesive or mixed, neuroendocrine to solid and undifferentiated carcinoma, with a predilection to the latter two ( P  < 0.001). De‐differentiation‐like transition and rhabdoid features were noted in a minority of cases. For overall survival, altered SMARCA4 expression was an unfavourable prognostic factor in stage III, EBV‐associated GC and non‐EBV/MSI intestinal subtype ( P  ≤ 0.001). SMARCA4 or ARID1A mutations were detected mainly in SMARCA4‐lost or reduced GC, respectively. Conclusions: SMARCA4‐altered GCs are rare and have intratumoral heterogeneity, histomorphological diversity, conditional prognostic significance and various genetic drivers. SMARCA4‐lost GC may represent a genuine SMARCA4‐deficient neoplasm, but most SMARCA4‐reduced/heterogeneous cases are secondary to ARID1A collapse or associated with different genotypes.